Evaluation with (De) Motivation: Array - Botezatu, Vanina Narcisa; Nicolae, Gabriela Florentina (Acta Universitatis Danubius. Relationes Internationales, 2021)
In this article, we will talk about how much the evaluation experience may or may not be motivating. We will describe what could be the main errors that can be made in the evaluation of subjective and objective testing and what strategies could be adopted to avoid falling into such errors, as well as what the teacher can do to make the moment of evaluation a motivating experience.